Las políticas de reparación simbólica a las víctimas del conflicto armado interno: Avances en el caso de Accomarca, Ayacucho - Garrido Espíritu, Geraldine Yolanda (2021)
In 2003, the Final Report of the Truth and Reconciliation Commission was delivered, which gathered around 7,300 testimonies from victims of the internal armed conflict that took place between 1980 and 2000 in Peru. Based on what was collected, recommendations and reflections were provided with the idea of generating a new citizenship and reforming institutions to prevent violence and respect human rights. However, these actions need a process of recognizing the victims and providing them with a suitable process of justice and reparation. This article addresses part of the investigation that is still in process on the symbolic reparations program in the Accomarca district of the Ayacucho region is presented, which continues to await the construction of a place of memory to remember, house and find the memories, experiences and struggles of their community.